ZnS@BSA Nanoclusters Potentiate Efficacy of Cancer Immunotherapy (Adv. Mater. 49/2021). Issue 49 (7th December 2021) - Cen, Dong; Ge, Qiwei; Xie, Congkun; Zheng, Qiang; Guo, Jiansheng; Zhang, Yuqi; Wang, Yifan; Li, Xiang; Gu, Zhen; Cai, Xiujun
Abstract : Cancer Therapy In article number 2104037, Xiang Li, Zhen Gu, Xiujun Cai, and co‐workers report that the generated H2 S and released zinc ions from ZnS@BSA nanoclusters promote accumulation of reactive oxygen species to activate cGAS/STING signals in tumor cells. ZnS@BSA nanoclusters are further demonstrated to facilitate antitumor immunotherapy by immune cell infiltration, showing potential for clinical translation.